Tecnologia do imaginário : o jornalismo como promotor das doenças mentais - Gomes, Denise Cristina Ayres (2016)
The thesis deals with journalism as "imaginary technology" (SILVA, 2012), a device that tends to promote mental illness to circumscribe the phenomenon and produce widespread sense in the social, creating ambience. Suffering is increasingly medicalized, technicized and mediatized in postmodernity. We left the Maffesoli notions that seem to translate postmodernity as the saturation of identity (2006, 2010c), the tragic (2003) and the body paroxysmal, resulting notion of presenteeism (2003). We use the bibliographic and documentary research and the comprehensive method by Michel Maffesoli (2010a) to understand how journalism tends to modulate emotions and behaviors. The corpus consists of twelve subjects, eight for 2001 and four 2011. The events were published in the printed version of the Folha de S. Paulo, also available in digital format. We understand that journalism serves as "imaginary technology" to spread "imaginary illness"; be installed as "therapeutic space"; and reveal an environment that cultivates the performance related to the productive capacity and emotional balance.